2017
DOI: 10.1149/07706.0133ecst
|View full text |Cite
|
Sign up to set email alerts
|

Adjoint Method for Increasing the Breakdown Voltage and Reducing the On-State Resistance in Wide Band Gap Power Transistors

Abstract: In this article we introduce a mathematical algorithm for the optimization of the doping distribution in power semiconductor devices in order to increase the breakdown voltage and decrease the on-state resistance of these devices. The algorithm is based on the computation of the doping sensitivity functions of the breakdown voltage and on-state resistance and uses a gradientbased iterative method to compute the optimum doping profile in metal-oxide-semiconductor field-effect transistors (MOSFET), insulted gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In the case of finite element models, which often require the IGBTs to be discretized in around 10 4 nodes, the computation time required for the evaluation of the doping sensitivity function becomes unpractical even on large computer clusters since the number of nodes is relatively large. Therefore, in this work we use an algorithm based on the adjoint method, algorithm that we developed previously in ( 6)- (8). Below, we summarize the most important results, but the reader can consult the above references for more information.…”
Section: Calculation Of Doping Sensitivity Function Of Breakdown Voltagementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of finite element models, which often require the IGBTs to be discretized in around 10 4 nodes, the computation time required for the evaluation of the doping sensitivity function becomes unpractical even on large computer clusters since the number of nodes is relatively large. Therefore, in this work we use an algorithm based on the adjoint method, algorithm that we developed previously in ( 6)- (8). Below, we summarize the most important results, but the reader can consult the above references for more information.…”
Section: Calculation Of Doping Sensitivity Function Of Breakdown Voltagementioning
confidence: 99%
“…In addition, we denote the magnitude of the electric field in the semiconductor at breakdown by   E, XD . Using these notations, it can be shown that the doping sensitivity function of the breakdown voltage is equal to   E  r can be evaluated by solving the following linear system of equations [8] where g is the unknown variable and X F is the Jacobian of the discretized system of governing equations and, then, calculating [9] where E  are the vector discretized values of   E  r and D F are the derivatives of the governing equations with respect to the doping concentration.…”
Section: Calculation Of Doping Sensitivity Function Of Breakdown Voltagementioning
confidence: 99%
“…This method is based on small-signal perturbations and completely circumvents the above drawbacks of the direct method. For more information about how to utilize the adjoint method to compute the sensitivity functions in power devices we recommend (1).…”
Section: Numerical Computation Of the Doping Sensitivity Functionsmentioning
confidence: 99%
“…We have recently presented a method for the optimization of the doping profiles to increase the breakdown voltage (V BR ) and decrease the on-state resistance (R ON ) in power semiconductor devices (1). The method is based on computing the doping sensitivity functions of V BR and R ON and using these sensitivity functions to perform a gradientbased optimization of the doping profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation